Analysis of Globodera rostochiensis effectors reveals conserved functions of SPRYSEC proteins in suppressing and eliciting plant immune responses - Moffett, Peter; Ali, Shawkat; Magne, Maxime; Chen, Shiyan; Obradovic, Natasa; Jamshaid, Lubna; Wang, Xiaohong; Bélair, Guy (Frontiers in Plant Science, 2015)
Potato cyst nematodes (PCNs), including Globodera rostochiensis (Woll.), are important pests of potato. Plant parasitic nematodes produce multiple effector proteins, secreted from their stylets, to successfully infect their hosts. These include proteins delivered to the apoplast and to the host cytoplasm. A number of effectors from G. rostochiensis predicted to be delivered to the host cytoplasm have been identified, including several belonging to the secreted SPRY domain (SPRYSEC) family. SPRYSEC proteins are unique to members of the genera Globodera and have been implicated in both the induction and the repression of host defense responses. We have tested the properties of six different G. rostochiensis SPRYSEC proteins by expressing them in Nicotiana benthamiana and N. tabacum. We have found that all SPRYSEC proteins tested are able to suppress defense responses induced by NB-LRR proteins as well as cell death induced by elicitors, suggesting that defense repression is a common characteristic of members of this effector protein family. At the same time, GrSPRYSEC-15 elicited a defense response in N. tabacum, and tobacco was found to be resistant to a virus expressing GrSPRYSEC-15. These results suggest that SPRYSEC proteins may possess characteristics that allow them to be recognized by the plant immune system.